2011
DOI: 10.1371/journal.pone.0028498
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary Essential Amino Acids Affect the Reproduction of the Keystone Herbivore Daphnia pulex

Abstract: Recent studies have indicated that nitrogen availability can be an important determinant of primary production in freshwater lakes and that herbivore growth can be limited by low dietary nitrogen availability. Furthermore, a lack of specific essential nitrogenous biochemicals (such as essential amino acids) might be another important constraint on the fitness of consumers. This might be of particular importance for cladoceran zooplankton, which can switch between two alternative reproductive strategies – the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 47 publications
2
50
1
Order By: Relevance
“…It has, however, been previously reported that EAA and protein deficiencies trigger the induction of sexual reproduction in cladoceran zooplankton, leading to stronger effect on offspring production and population size than on somatic growth (Koch et al, 2009(Koch et al, , 2012Fink et al, 2011;Bouchnak and Steinberg, 2014). In our study, the protein content, as well as the amount of NEAA, boosted the somatic growth of Daphnia when sterols were adequate (see GLM results on Table 3), but direct connections between proteins, EAAs or NEAAs and reproduction could not be detected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has, however, been previously reported that EAA and protein deficiencies trigger the induction of sexual reproduction in cladoceran zooplankton, leading to stronger effect on offspring production and population size than on somatic growth (Koch et al, 2009(Koch et al, , 2012Fink et al, 2011;Bouchnak and Steinberg, 2014). In our study, the protein content, as well as the amount of NEAA, boosted the somatic growth of Daphnia when sterols were adequate (see GLM results on Table 3), but direct connections between proteins, EAAs or NEAAs and reproduction could not be detected.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoplankton is in general rich in AAs, but the AA profiles can differ significantly between even closely related species (Brown et al, 1997;Koch et al, 2012). For zooplankton, the essential AAs are considered to be the same as for insects and humans (Supplemental Table 2; Fink et al, 2011). In cladoceran zooplankton, the availability of dietary proteins and essential amino acids (EAAs) has been connected to resting egg production rather than to somatic growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Females, in particular, require large supplies of amino acids for synthesizing egg yolk (Dimond et al, 1956). Restriction of amino acids thus has a direct impact on female fecundity (Chang, 2004; Dimond et al, 1956; Fink et al, 2011). Amino acid deprivation also significantly affects larval growth and development, as well as adult life span (Baltzer et al, 2009; Britton and Edgar, 1998; Chang, 2004; Grandison et al, 2009; Vrzal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…• C for 24 h. Samples were neutralized with 200 µl of an alkaline solution (5 M KOH, 1 M triethanolamine) and centrifuged at 11,000 × g for 10 min to remove precipitated perchlorate (Fink et al 2011). Subsequently, 20 µl of the supernatant were transferred into a HPLC vial and diluted with 180 µl ultrapure water.…”
Section: Amino Acid Determinationmentioning
confidence: 99%